Application of analgesics in emergency services in Germany: a survey of the medical directors - Signe Vilcane; Olga Scharonow; Christian Weilbach; Maximilian Scharonow (BMC Emergency Medicine)
Abstrac Background Treatment of acute pain is an essential element of pre-hospital care for injured and critically ill patients. Clinical studies indicate the need for improvement in the prehospital analgesia. Objective The aim of this study is to assess the current situation in out of hospital pain management in Germany regarding the substances, indications, dosage and the delegation of the use of analgesics to emergency medical service (EMS) staff. Material and methods A standardized survey of the medical directors of the emergency services (MDES) in Germany was carried out using an online questionnaire. The anonymous results were evaluated using the statistical software SPSS (Chi-squared test, Mann-Whitney-U test). Results Seventy-seven MDES responsible for 989 rescue stations and 397 EMS- physician bases in 15 federal states took part in this survey. Morphine (98.7%), Fentanyl (85.7%), Piritramide (61%), Sufentanil (18.2%) and Nalbuphine (14,3%) are provided as opioid analgesics. The non-opioid analgesics (NOA) including Ketamine/Esketamine (98,7%), Metamizole (88.3%), Paracetamol (66,2%), Ibuprofen (24,7%) and COX-2-inhibitors (7,8%) are most commonly available. The antispasmodic Butylscopolamine is available (81,8%) to most rescue stations. Fentanyl is the most commonly provided opioid analgesic for treatment of a traumatic pain (70.1%) and back pain (46.8%), Morphine for visceral colic-like (33.8%) and non-colic pain (53.2%). In cases of acute coronary syndrome is Morphine (85.7%) the leading analgesic substance. Among the non-opioid analgesics is Ketamine/Esketamine (90.9%) most frequently provided to treat traumatic pain, Metamizole for visceral colic-like (70.1%) and non-colic (68.6%) as well as back pain (41.6%). Butylscopolamine is the second most frequently provided medication after Metamizole for “visceral colic-like pain” (55.8%). EMS staff (with or without a request for presence of the EMS physician on site) are permitted to use the following: Morphine (16.9%), Piritramide (13.0%) and Nalbuphine (10.4%), and of NOAs for (Es)Ketamine (74.1%), Paracetamol (53.3%) and Metamizole (35.1%). The dosages of the most important and commonly provided analgesic substances permitted to independent treatment by the paramedics are often below the recommended range for adults (RDE). The majority of medical directors (78.4%) of the emergency services consider the independent application of analgesics by paramedics sensible. The reason for the relatively rare authorization of opioids for use by paramedics is mainly due to legal (in)certainty (53.2%). Conclusion Effective analgesics are available for EMS staff in Germany, the approach to improvement lies in the area of application. For this purpose, the adaptations of the legal framework as well as the creation of a guideline for prehospital analgesia are useful.